2016
DOI: 10.1186/s12909-016-0777-z
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of empathy in pre-clinical and clinical medical students and clinical supervisors

Abstract: BackgroundAlthough appropriate empathy in health professionals is essential, a loss of empathy can occur during medical education. The structure of clinical learning may be one factor that is implicated in a loss of empathy. This study examines student and doctor empathy, and possible associations between empathy and the structure of clinical learning.MethodsThere were three groups of participants: medical students (n = 281), who completed a longitudinal survey consisting of the Jefferson Scale of Empathy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 23 publications
2
44
1
4
Order By: Relevance
“…They feel a strong urge to continuously grow and identify effective feedback as a means toward this goal (Luthar, 2017;Chung et al, 2018;Mestdagh et al, 2018). Complementary studies have corroborated that providing effective feedback enabled students to experience a greater sense of volitional (Joshi et al, 2017;Oommen et al, 2017;Mestdagh et al, 2018) and psychological freedom (Cubi-Molla et al, 2018), an increased sense of fulfillment of personal effectiveness (Holaday et al, 1994;Mahoney et al, 2016) and improved social relatedness (Fond et al, 2018), and interpersonal relationships (Ottenberg et al, 2016;Hill et al, 2018). In addition, effective feedback has been reported to augment feelings of self-perceived academic competency (Younan, 2016;Brass et al, 2017;Everson et al, 2018), enhance defensive coping styles (Bhagat et al, 2015;Jacobs et al, 2015;Cant and Cooper, 2017), and increase IM to attend and participate in class (Bradley et al, 2012;Mabel and Britton, 2018).…”
Section: Bridge Generational Issues Between Educators and Studentsmentioning
confidence: 99%
See 3 more Smart Citations
“…They feel a strong urge to continuously grow and identify effective feedback as a means toward this goal (Luthar, 2017;Chung et al, 2018;Mestdagh et al, 2018). Complementary studies have corroborated that providing effective feedback enabled students to experience a greater sense of volitional (Joshi et al, 2017;Oommen et al, 2017;Mestdagh et al, 2018) and psychological freedom (Cubi-Molla et al, 2018), an increased sense of fulfillment of personal effectiveness (Holaday et al, 1994;Mahoney et al, 2016) and improved social relatedness (Fond et al, 2018), and interpersonal relationships (Ottenberg et al, 2016;Hill et al, 2018). In addition, effective feedback has been reported to augment feelings of self-perceived academic competency (Younan, 2016;Brass et al, 2017;Everson et al, 2018), enhance defensive coping styles (Bhagat et al, 2015;Jacobs et al, 2015;Cant and Cooper, 2017), and increase IM to attend and participate in class (Bradley et al, 2012;Mabel and Britton, 2018).…”
Section: Bridge Generational Issues Between Educators and Studentsmentioning
confidence: 99%
“…This often leads to professional burnout, a multifactorial syndrome, characterized by high levels of emotional exhaustion, depersonalization, and a reduced sense of personal accomplishment (Walker et al, 2016;Chen et al, 2017;Pape et al, 2018). Studies have reported that even having one burnout symptom can cause negative effects that not only interfere with learning (Mohr et al, 2011;Lopes et al, 2015;Lowe et al, 2016), but can also cause physical (Mahoney et al, 2016) and psychological symptoms (de Paiva et al, 2017;Fond et al, 2018), and even the use of illicit drugs (Brown et al, 2016;Merrill and Carey, 2016;Chen et al, 2017). Recent studies have reported that the development of burnout in health care students can be directly related to low levels of IM in these students (Rosenman et al, 2014;Lowe et al, 2016;Fond et al, 2018;Worly et al, 2018).…”
Section: Challenges Of Present-day Health Care Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…This transformative process toward internalization of “the way of being a physician,” or professional identity formation (PIF), is influenced by multiple factors in a student's professional and personal life . Clinical experience is a particularly influential factor in a students’ PIF and introduces students to new realities that may conflict with their previously formed ethical ideals and have the potential to lead to burnout and diminished empathy . As such, it is important that educators understand how students are experiencing the clinical environment to best guide them in their PIF.…”
mentioning
confidence: 99%